Benign and malignant skin lesions in patients attended in a public hospital in Trujillo, Peru - Vilela-Desposorio, Carlos (2023)
Objective: To determine the clinical and socio demographic features of patients attended at a public hospital in Trujillo, Peru. Methods: A cross-sectional study that included 385 skin biopsies obtained from the archives of the Pathology Department and from the clinical charts of these patients at Hospital Belen in Trujillo from January 2018 to December 2019 was carried-out. Results: The most common entity was basocellular carcinoma located on the face in patients above 60 years of age. The second most common entity was epidermoid carcinoma. Malignant lesions affected 66.7% of patients between 55 and 79 years of age with a mean of 67 years. Most of the patients were unemployed males (65.8%). The most common benign lesion was the epidemic inclusion cyst mostly in the trunk among males from 20 to 24 years of age. The second most common benign lesion was the pilomatrixoma mostly located in the upper limbs of patients below 10 years of age. Benign lesions affected the 59.6% of the sample between 30 to 54 years of age with a mean of 44 years, mostly among housewives. Most of the patients came from districts of Trujillo. The causal agent was not identified. Conclusions: In mestizo patients both benign and malignant lesions had a clinical presentation similar as reported in the literature regarding location, age and gender distribution. Occupation and precedence were not contributory.